185k views
4 votes
Combine like terms:

-3(4x + 3) - (2x - 5) + 6(3x - 4)
Make sure you put your x term first
Due in 6 hours

2 Answers

3 votes
So we have to use the distributive property:

We ll get -12x-9-2x+5+18x-24
Now we have to combine like terms
-12-2x+18x=4x
-9+5-24=-28
Therefore our answer is:
Y=4x-28
User Amirreza Nasiri
by
5.1k points
7 votes

Answer:

4x - 28

Explanation:


-3(4x + 3) - (2x - 5) + 6(3x - 4)


\mathrm{Apply\:the\:distributive\:law}:\quad \:-\left(a-b\right)=-a+b


-\left(2x-5\right)=-2x+5


=-3\left(4x+3\right)-2x+5+6\left(3x-4\right)


=-12x-9-2x+5+6\left(3x-4\right)


=-12x-9-2x+5+18x-24


\mathrm{Group\:like\:terms}


=-12x-2x+18x-9+5-24


\mathrm{Add\:the\:numbers:}\:-9+5-24=-28


=-12x-2x+18x-28


\mathrm{Add\:similar\:elements:}\:-12x-2x+18x=4x


=4x-28

~Learn with Lenvy~

User Henry Keiter
by
4.6k points